“THE RURAL INDIA”. Representations of the Village Identity in the System of British Colonial Knowledge - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2003)
The article explores one topic in the system of colonial knowledge of the 19th century British India which concerns understanding and interpreting Indian village communities and village identity as it is dealt with in the British social theory. The first part of the article is devoted to the critical overview of the forms of colonial knowledge and numerical thinking which undergrounds them. It helps to point out that the constructed identity of “village” India is an indispensable part of the overall colonial strategy of empirical knowledge and administration which enabled later to approve the theoretical representations of India as consisting of autonomous village societies. In the second part of the article, while exploring the analysis of colonial knowledge, the attempt is made to show the possible approaches to yet scarcely examined problem of how the image of “village” India was used to represent the conceptions of the historiography of Indian art and art education in British India. The institutionalized position in the Indian art schools of ornamental design starting with early the 19th century was labelled particularly to the activity of village communities. As a result, its theoretical approval in the definition of fine and applied arts can be taken as one of the references, which guide to the exploration of the problem about the main impulses collecting and describing objects of art as amateurs’ production in the early colonial period as a part of the system of empirical knowledge.